A produção acadêmica sobre estágio supervisionado na formação de professores : o que revelam os textos dos ENDIPES de 2000 a 2012 - Casotte, Liliane Dias Heringer (2016)
In this research we propose to map, describe and analyze the academic production on Supervised Internship in teacher training, presented at the Encontros Nacionais de Didática e Prática de Ensino (Endipes). The focus of the research was based on the development of a state of knowledge on the said topic in the period 2000 to 2012. We have developed a bibliographical documentary research, qualitative and quantitative basis, which carried out a mapping study on the subject Supervised Internship in Endipes that period, taking it as significant relevant issues in the scientific field of education. The Supervised Training has been highlighted in the research setting on teacher training for its mighty contribution to both the promotion for the relationship between theory and practice in training and teaching work, and for the constitution of the teaching identity and for the development of collaborative actions between universities and basic education schools, since, during the Supervisd Internship, the graduating have the opportunity to experience teaching and learning situations and reflect about the educational practice at the same time that he/she formed as a teacher and researcher of his/her professional activity. Thus, we dialogued with productions Pimenta (2001, 2002 and 2011), Pimenta and Lima (2004 and 2011), Lima (2012) and Nóvoa (1992, 2004 and 2009). The results of the materiality show the collaboration of Endipes for the socialization of production, since it brings together results of the work of researchers around the country. In this scenario, through the texts presented in the panel mode in the period from 2000 to 2012, the Supervised Internship is highlighted as significant curricular component, effective to promote the relationship between theory and practice and collaborative action between university and school, as well as for the reflexive teacher training, for the establishment of teacher identity and the composition of the teaching knowledge. In addition to these issues, the authors also dealt with the experiences of Supervised Internship and occupied in analyzing the underlying rationales for teacher training conceptions.